Implications of Money Laundering From Corruption Proceeds on The Application of Reverse Evidence in Corruption Crimes - Lindasari, Lindasari (Corruptio, 2023)
Corruption is one of the Extra Ordinary Crimes because of the difficulty of proving the crime by law enforcement. In the enforcement and eradication of corruption crimes, there are several problems faced, one of which is in settlement of corruption crimes through juridical settlement, namely the existence of an evidentiary process that is considered complex in court and as minimal as possible does not damage the protection and honor of human rights.  The United Kingdom and other European countries have used civil channels to return assets resulting from money laundering crimes, while Indonesia is still returning assets from money laundering crimes, meaning there is no return of any assets before a court decision. It takes courage from related law enforcement in the criminal act of money laundering by using the reverse burden of proof in the law of proving money laundering cases. This study aims to determine the application of reverse proof in corruption cases. This research uses normative legal research methods. The results of the study The application of reverse proof requires review because, in reverse proof, the defendant must prove that his property is not a crime of corruption. The application of the reverse proof policy is that most of the assets owned by the bribe giver are not in the name of the briber but have been suspected of money laundering to hide the original identity of the assets derived from the proceeds of corruption.